Green bonds' reputation effect and its impact on the financing costs of the real estate sector - Aleksandar Petreski; Dorothea Schäfer; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper explores the effect of a firm's reputation of being a green bond issuer on its financing costs. Using a sample of 73 listed Swedish real estate companies issuing in total about 1500 bonds over the period from 2011 till 2021, differencein- difference analyses and instrumental variable estimations are applied to identify the causal impact of frequent green vis-à-vis frequent non-green bond issuing on a firm's cost of capital and credit rating. The paper argues that it is repetitive issuance which lowers a firm's cost of capital, while the effects from first or one-time green bond issuance is the opposite. In line with the reputation capital hypothesis, issuing green bonds even lowers the firm's cost of equity capital, while issuing non-green bonds has no effect on the cost of equity capital.
Keywords: G32; R30; R32; 330; bond issuance; green debt; reputation capital; sustainability; ESG